Issues in Erp implementation and computerized banking system - Zainol, Zaini; Malami, Abu Bakar (IIUM Press, International Islamic University Malaysia, 2017)
In the first part of this ebook (chapter 1-3), the discussion is about Enterprise Resource Planning (ERP). ERP is an information system that manages, through integration, all aspects of a business including production planning, purchasing, manufacturing, sales, distribution and accounting. In Malaysia the local companies are being encouraged to adopt ERP through the availability of financial assistance by many governmental bodies. However, there lies an important question how ERP systems are being selected and adopted in the companies. Questions related to appropriateness of software to purchase, software suitability company, appropriate ways of implementation, decision to maintain or do away with the old system, projected ERP benefits, maintenance issues and standardization need answers and the question is where or who does the company turns to for these answers. Therefore, the intention of this research is to provide sufficient documentation that aims to reduce these uncertainties with regards to ERP project investment by providing possible answers and eventually propose a decision support system that makes ERP decision making an informed process. For the second part of this ebook (chapter 4-10), the discussion is about threats and security controls in computerized banking system.